A Study On Attitude Of Policyholders Of Lic Of India With Special Reference To Perambalur District - Rani, Dr. A. Jesintha (The journal of contemporary issues in business and government, 2021)
The present study analyzes the attitude of policyholders of Life Insurance Corporation of India with special reference to Perambalur district, the data were collected and analysed as per the requirement of the study. The primary data were collected from the respondents through questionnaire method. The study has adopted convenience sampling method for selecting 454 respondents. The results revealed the fact that the factors, income, education, occupation and awareness have influenced the level of attitude of the policyholders.